Man and Wild Elephant Conflict in Orissa - Swain, Debabrata (Indian Forester, 2001)
Man and Wild Elephant conflict is as old as human civilization. With the increase in human population and fragmentation of Elephant habitats this is felt more frequent at present than ever before. In this paper crop raiding of Elephants and human deaths due to Elephants in Orissa have been discussed. Out of 275.8 ha of crop damaged during 1990.1991 and 1995-1996, paddy constituted over 200 ha. Next to paddy was Sugarcane covering about 20 ha and remaining 55 ha had crops like maize, ragi, coconut plantation etc. Similarly, human deaths due to attack by wild Elephants in Orissa were 74 and injury to 21 persons. The causes of man-wild Elephant conflict are encroachment of Elephant lands by human, conflict due to migration of Elephants, delicacy of crops and intoxication of Elephants due to brewed Rice and Mahua flower and shortage of water inside the forested area. For the resolution of man-wild Elephant conflict it is suggested to construct Elephant-proof barriers, removal of encroachments, especially on their corridors of migration, provision of water where scarcity of water occurs during summer, capture of rogue and troublesome Elephants, social security schemes against damages caused by Elephants, education of the interface people and ecotourism.